Oncocytic Polyp in a Unicystic Mucoepidermoid Carcinoma of the Palate: A Unique Presentation. (February 2022) - Ito, Yumi; Nishimura, Michiko; Kikuchi, Kentaro; Hamada, Yoshiki; Ogawa, Ikuko; Ide, Fumio
We report a palatal mucoepidermoid carcinoma (MEC) with unusual pathological features showing salivary duct cyst-like architecture, varied epithelial linings (excretory duct, mucous goblet cell, and apocrine epithelium phenotypes), scarce luminal tumor plaques, and a large intraluminal oncocytic polyp. To our knowledge, such a unicystic variant of MEC with pedicled oncocytic proliferation in the lumen is unprecedented in the literature. In this particular case, the microscopic diagnosis of MEC is problematic because of the large number of potential mimics.